Sex steroid receptor expression and localization in benign prostatic hyperplasia varies with tissue compartment - Nicholson, Tristan M. (2013)
Androgens and estrogens, acting via their respective receptors, are important in benign prostatic hyperplasia (BPH). The goal of this study was to quantitatively characterize the tissue distribution and staining intensity of androgen receptor (AR) and estrogen receptor-alpha (ERα), and assess cells expressing both AR and ERα, in human BPH compared to normal prostate. A tissue microarray composed of normal prostate and BPH tissue was used and multiplexed immunohistochemistry was performed to detect AR and ERα. We used a multispectral imaging platform for automated scanning, tissue and cell segmentation and marker quantification. BPH specimens had an increased number of epithelial and stromal cells and increased percentage of epithelium. In both stroma and epithelium, the mean nuclear area was decreased in BPH relative to normal prostate. AR expression and staining intensity in epithelial and stromal cells was significantly increased in BPH compared to normal prostate. ERα expression was increased in BPH epithelium. However, stromal ERα expression and staining intensity was decreased in BPH compared to normal prostate. Double positive (AR & ERα) epithelial cells were more prevalent in BPH, and fewer double negative (AR & ERα) stromal and epithelial negative cells were observed in BPH. These data underscore the importance of tissue layer localization and expression of steroid hormone receptors in the prostate. Understanding the tissue-specific hormone action of androgens and estrogens will lead to a better understanding of mechanisms of pathogenesis in the prostate and may lead to better treatment for BPH.